2003
DOI: 10.1037/0278-7393.29.6.1051
|View full text |Cite
|
Sign up to set email alerts
|

Is Temporal Spacing of Tests Helpful Even When It Inflates Error Rates?

Abstract: The occurrence of errors is often thought to impede associative learning. This was tested in 2 studies, each of which involved 2 sessions. In Session 1, subjects learned foreign vocabulary (Experiment 1) or obscure English words (Experiment 2) and received 2 tests (each with corrective feedback) separated by a variable lag. Greater lags drastically reduced performance on the 2nd test. However, they dramatically improved performance in a Session-2 test given 1 day (Experiment 1) or 1 week later (Experiment 2). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
98
1
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(104 citation statements)
references
References 29 publications
4
98
1
1
Order By: Relevance
“…Errorless learning has had a long and influential history in psychology (e.g., Guthrie, 1952;Skinner, 1958). Although it is an idea that derives mainly from findings in studies of nonhuman animal learning, it has influenced suggestions about best practices for educators as well (for a discussion, see Pashler, Zarow, & Triplett, 2003), and it is used frequently and successfully in patient populations (e.g., Evans et al, 2000).…”
Section: Are the Effects Of An Unsuccessful Testmentioning
confidence: 99%
See 1 more Smart Citation
“…Errorless learning has had a long and influential history in psychology (e.g., Guthrie, 1952;Skinner, 1958). Although it is an idea that derives mainly from findings in studies of nonhuman animal learning, it has influenced suggestions about best practices for educators as well (for a discussion, see Pashler, Zarow, & Triplett, 2003), and it is used frequently and successfully in patient populations (e.g., Evans et al, 2000).…”
Section: Are the Effects Of An Unsuccessful Testmentioning
confidence: 99%
“…Making such a comparison is difficult, however, because of item-selection effects: In a test condition, it is easy to select items that were not recalled successfully (i.e., nonretrievable items), but selecting nonretrievable items is not possible in a read-only condition because there is no recall test. As Pashler et al (2003) …”
Section: Are the Effects Of An Unsuccessful Testmentioning
confidence: 99%
“…Our results have only indirect implications for such programs, but they suggest that conditions that produce the fewest errors during learning (like massed practice in Experiments 1 and 2) can lead to very poor long-term retention. Delaying an initial test, thereby making an initial retrieval attempt more difficult, leads to more errors on the test but also produces the biggest gains in long-term retention, especially when feedback is given to correct errors committed on the delayed first test (see too Pashler et al, 2003). We think that comparison of specific schedules of spaced practice may be important for determining which memory training techniques are most effective, and on the basis of our results, equally spaced practice appears to be more effective than expanding retrieval.…”
Section: Implications For Memory Training and For Enhancing Student Lmentioning
confidence: 99%
“…However, in our study and in Spitzer's, students were not given feedback after the tests. If students receive feedback after tests, as they would if they were testing themselves and spacing their practice over several days in preparation for an upcoming exam, then a delayed first test might benefit learning more than an immediate test, despite poorer performance on the delayed test (see too Pashler et al, 2003). The issue of what the optimal delay should be before a first retrieval attempt to promote learning of different types of materials awaits future research.…”
Section: Implications For Memory Training and For Enhancing Student Lmentioning
confidence: 99%
“…To the extent that spacing induces forgetting, it also increases the likelihood of recalling incorrect information. And although research has shown that when learners are given feedback, the benefits of spacing can overwhelm the potentially harmful effect of generating incorrect information (e.g., Pashler, Zarow, & Triplett, 2003), when feedback is not given, the repeated retrieval of incorrect information may propagate those errors into the future (e.g., Toppino & Brochin, 1989). By testing immediately, and then systematically introducing spacing between repeated tests, it is possible and likely that the number of errors can be minimized.…”
Section: Error-reduction Benefits Of Expanding Retrieval Practicementioning
confidence: 99%